2016
DOI: 10.1371/journal.pone.0163754
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Long-Term Relative Survival in Females and Younger Adults Undergoing Cardiac Surgery: A Prospective Cohort Study

Abstract: ObjectivesTo assess long-term survival and mortality in adult cardiac surgery patients.Methods8,564 consecutive patients undergoing cardiac surgery in Trondheim, Norway from 2000 until censoring 31.12.2014 were prospectively followed. Observed long-term mortality following surgery was compared to the expected mortality in the Norwegian population, matched on gender, age and calendar year. This enabled assessment of relative survival (observed/expected survival rates) and relative mortality (observed/expected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
7
1
4
Order By: Relevance
“…A study from Trondheim, Norway from 2016 followed patients that had undergone CABG, aortic valve replacement (AVR) or both. This study reported that female patients and patients in the age groups under 60 years and 60-69 years had reduced long-term survival compared to the general population, while male patients older than 70 years had improved survival [20]. The findings regarding female patients, male patients older than 70 years and patients in the age group 60-69 years differs from the findings in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…A study from Trondheim, Norway from 2016 followed patients that had undergone CABG, aortic valve replacement (AVR) or both. This study reported that female patients and patients in the age groups under 60 years and 60-69 years had reduced long-term survival compared to the general population, while male patients older than 70 years had improved survival [20]. The findings regarding female patients, male patients older than 70 years and patients in the age group 60-69 years differs from the findings in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…There was a clear negative impact of known risk factors [ 14 ], such as diabetes, COPD, heart failure, reduced renal function and smoking at the time of surgery, both for observed and relative survival. Observed and relative survival were reduced in patients with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in coronary surgery without AVR have repeatedly shown that surgery has a substantial effect on the mortality risk of CAD. In a Norwegian population, Enger et al [ 14 ] showed that CABG conveyed persistently better relative survival than that in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The benefit of female gender for longer life expectancies than men is lost when they undergo cardiac surgery. 43 It is difficult to determine the reason why women experience higher mortality than men post-cardiac surgery. Although some studies have stated that transfusion or RBC is an independent risk factor for mortality, others have shown that transfusion may play a secondary role and that other undetermined factors related to gender may also be important.…”
Section: Discussionmentioning
confidence: 99%